Persuasive strategies in grant recommendation letters written by senior faculty in a Ghanaian university - Benjamin Archibald Afful , Joseph; Kwesi Hesse, Eugene; Agbaglo, Ebenezer; Mensah Bonsu, Emmanuel (ExELL, 2025)
The genre system of grant application has gained attention from researchers in Applied Linguistics, Discourse Studies, and Higher Education. However, the grant recommendation letter (GRL), also known as the “letter of support”, has been understudied in this system. To address this gap, this study examined the persuasive strategies used in GRLs. Using Aristotle’s Theory of Persuasion and a qualitative inductive discourse analysis, we analysed 90 GRLS. The findings revealed that GRLs employ different frequencies of ethos, logos, and pathos to influence the grant committee. The writers primarily emphasised rational justifications for the applicant’s qualifications, while also demonstrating ethos through appropriate personal traits. Personal pronouns were used to perform discursive functions as well. Based on the findings, we offer implications for pedagogy and further research on GRLs.